The chameleon in consumers: Development and validation of a scale to measure Consumers' Cognitive Flexibility - Nadine Benninger; Jutta Roosen (Psychology & Marketing, 2024)
This paper introduces a new scale, the Consumers' Cognitive Flexibility Scale (CCF-Scale). Consumers' Cognitive Flexibility (CCF) is conceptualized as the adaptation~to changes in the environment and to product options by exhibiting flexible thoughts, feelings, and actions. This scale is a new measure of consumers' mental capabilities to understand and evaluate unknown products. Especially, really new products (RNPs) are highly innovative and different from well-known products in the market. A flexible mindset can help integrate RNPs into existing knowledge structures. The CCF-Scale was developed and tested with four prestudies and four representative studies with 1057, 696, 494 German, and 506 US consumers. The prestudies were used to ensure face and content validity and to select products for criterion validity. The findings demonstrate a reliable and valid scale in both countries consisting of 14 items with three CCF-facets: Coping (with consumption problems), Perspective (change for product/information evaluation), and Alignment (to changes in the environment). Results show that the CCF-facets help explain RNP-acceptance across different categories (e.g., food, furniture, and digital services). One limitation is the article's focus on RNPs. Still, marketers can use these findings to adjust instructions on how to use RNPs and to communicate more effectively, for example by using analogies.
Keywords: 650; cognitive flexibility; consumer innovativeness; innovation acceptance; measurement; really new products; RNPs; scale development